THE USE OF DIFFERENTIAL EQUATIONS IN VECTOR OPTIMIZATION PROBLEMS - Bosov, O. O.; Bezsala, Ye. V.; Savchenko, L. M. (Science and Transport Progress, 2007)
Offered method of the differential equations in problem of the vector optimization.